VAMP3 and SNAP23 as Potential Targets for Preventing the Disturbed Flow-Accelerated Thrombus Formation - Zhu, Juan-Juan; Jiang, Zhi-Tong; Liu, Chen; Xi, Yi-Feng; Wang, Jin; Yang, Fang-Fang; Yao, Wei-Juan; Pang, Wei; Han, Li-Li; Zhang, Yong-He; Sun, An-Qiang; Zhou, Jing (Frontiers in Cell and Developmental Biology, 2020)
Disturbed blood flow has been recognized to promote platelet aggregation and thrombosis via increasing accumulation of von Willebrand factor (VWF) at the arterial post-stenotic sites. The mechanism underlying the disturbed-flow regulated endothelial VWF production remains elusive. Here we described a mouse model, in which the left external carotid artery (LECA) is ligated to generate disturbed flow in the common carotid artery. Ligation of LECA increased VWF accumulation in the plasma. Carotid arterial thrombosis was induced by ferric chloride (FeCl3) application and the time to occlusion in the ligated vessels was reduced in comparison with the unligated vessels. In vitro, endothelial cells were subjected to oscillatory shear (OS, 0.5 ± 4 dynes/cm2) or pulsatile shear (PS, 12 ± 4 dynes/cm2). OS promoted VWF secretion as well as the cell conditioned media-induced platelet aggregation by regulating the intracellular localization of vesicle-associated membrane protein 3 (VAMP3) and synaptosomal-associated protein 23 (SNAP23). Disruption of vimentin intermediate filaments abolished the OS-induced translocation of SNAP23 to the cell membrane. Knockdown of VAMP3 and SNAP23 reduced the endothelial secretion of VWF. Systemic inhibition of VAMP3 and SNAP23 by treatment of mice with rapamycin significantly ameliorated the FeCl3-induced thrombogenesis, whereas intraluminal overexpression of VAMP3 and SNAP23 aggravated it. Our findings demonstrate VAMP3 and SNAP23 as potential targets for preventing the disturbed flow-accelerated thrombus formation.